THE RELATIONSHIP OF DIET AND PHYSICAL ACTIVITY WITH THE INCIDENT OF HYPERUSEMIA IN THE ELDERLY IN KEH VILLAGE, NIBONG DISTRICT, NORTH ACEH DISTRICT - Mahruri Saputra; Aina Fitri; Suci Safitri (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Hyperuricemia includes a degenerative disease that attacks the joints Gout is a metabolic disorder characterized by increased uric acid (hyperuricemia). Food and drinks are one of the factors that can increase uric acid levels in the blood. Physical activity is the movement of the body due to the activity of the skeletal muscles which involves energy expenditure. The purpose of this study was to determine the relationship between diet and physical activity with the incidence of hyperusemia in the elderly in Keh Nibong Village. This study used quantitative research with a correlational design with a Cross Sectional approach. Theimplementation of this research was carried out on July 27 – August 1, 2023. The population is 42 patients. Tehnik sampling using total sampling. Data analysis in this study using Chi Square test and Kolmogorof Smirnov, the results showed that based on statistical tests (Chi-Square), obtained P-Value value = 0.001 (0.001 < 0.05) which means ho was rejected, it can be concluded that there is a significant relationship between diet and incidence hyperusemia in the elderly in Keh Village, Nibong District. An alternative test, Kolmogorov-Smirnov, obtained results with p values of 0.003 < 0.05, which means that there is a significant relationship between physical activity and the incidence of hyperusemia in the elderly in Keh Village, Nibong District.